2022
DOI: 10.3390/nu14051107
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Malnutrition Associated with Major Depressive Disorder from a Sex-Gender Perspective

Abstract: Major depressive disorder (MDD) is an incapacitating condition characterized by loss of interest, anhedonia and low mood, which affects almost 4% of people worldwide. With rising prevalence, it is considered a public health issue that affects economic productivity and heavily increases health costs alone or as a comorbidity for other pandemic non-communicable diseases (such as obesity, cardiovascular disease, diabetes, inflammatory bowel diseases, etc.). What is even more noteworthy is the double number of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 315 publications
0
11
0
1
Order By: Relevance
“…However, the global burden of MDD has been increasing during the last years, specially due to the coronavirus disease 2019 (COVID-19) pandemic ( 4 ). Likewise, the risk for suffering from MDD is 2-fold higher in woman than in men, showing some particularities in the underpinning biological mechanisms ( 5 ), and although the prevalence may vary across ages, this condition may appear virtually at any stage of life ( 6 ). Furthermore, MDD entails devastating individual and socioeconomic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…However, the global burden of MDD has been increasing during the last years, specially due to the coronavirus disease 2019 (COVID-19) pandemic ( 4 ). Likewise, the risk for suffering from MDD is 2-fold higher in woman than in men, showing some particularities in the underpinning biological mechanisms ( 5 ), and although the prevalence may vary across ages, this condition may appear virtually at any stage of life ( 6 ). Furthermore, MDD entails devastating individual and socioeconomic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Among the elderly, malnourished subjects were 31% more likely to have symptoms of depression than those with normal nutritional status[ 32 , 33 ]. Our results showed that nutritional deficiencies are 1.3 times higher in the depression cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in the elderly population requires investigating the characteristics of depression, which negatively affects social interaction, causes undernutrition, reduces the quality of life, causes pain, and has a significant economic impact due to high treatment costs. [7] Depression is a major global health problem characterized by symptoms such as altered mood, loss of interest and pleasure, and impairment in cognitive and physical functions. Patients hospitalized for medical conditions have a higher risk of depression than the general population.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%